Ophthalmic manifestations of Covid-19 and Mpox - potentially dangerous complications, and underdiagnosis by researchers and clinicians - Hyjek, Michał; Pierzchała, Jakub Rafał; Bednarz, Katarzyna; Banaś, Patryk; Sobańska, Natalia; Banasiak, Aleksandra Paulina; Teichman, Rafał; Kasprowicz, Jakub; Abram, Kamila; Adamus, Justyna (Quality in Sport, 2023)
Introduction: The Covid-19 pandemic and the increase in monkeypox (Mpox) infections that have been with us for the past two years have forced scientists and doctors to intensify their efforts to understand them. They mainly affect the respiratory, circulatory and immune systems and cause skin lesions. They can lead to death from lung disease, so complications such as ophthalmic ones are not often described in scientific studies, but doctors report that Covid-19 and Mpox patients not infrequently show symptoms such as inflammation, conjunctival congestion, corneal ulceration, swelling of the eye area and others. Aim of the study: The aim of this study was to review scientific articles with a view to presenting the problem of ocular complications following SARS-CoV-2 infection and ways to prevent them. Methods and materials: a literature review was conducted using the PubMed database, using the keywords: “ocular complications”, “ophthalmic complications” “ocular manifestations”, “eye complications”, “monkeypox”, “Mpox”, “Covid-19” “SARS-CoV-2”. Results: PCR studies from conjunctival swabs have confirmed the presence of SARS-COV-2 and MPXV genetic materials in ocular secretions, so they are a reservoir of viruses and pose a risk of further transmission. In the case of Covid-19, the eye can act as a host for infection. Humidification and preventive antibiotic therapy have been shown to prevent bacterial superinfection and avoid serious ocular complications, including loss of vision. Conclusions: Patients with Covid-19 and Mpox should be diagnosed ophthalmologically, as neglect can lead to deterioration and even loss of vision, reducing their quality of life. Eye care treatments and pharmacotherapy prevent future complications. It is also important to use personal protective equipment, take care of hygiene and disinfect equipment used for ophthalmic examinations to prevent the spread of infections to other patients as well as to medical staff.